PRODUCTIVITY AND EMPLOYEE NEEDS AT ECHELON IV FOOD CROPS, HORTUCULTURE AND ANIMAL HUSBANDRY OFFICE (IMPLEMENTATION OF PERMENDAGRI NO. 99 OF 2018) - Susi Desmaryani; Vinni aprilianti; Weni lestari; M. Rialdi Syaputra; Asti Harkeni; Enny Andriany (International Journal of Artificial Intelligence Research, 2022)
The productivity of echelon IV in the Food Crops, Horticulture, and Livestock Service is needed in implementing the program for providing food sources of protein. Protein is a nutrient that plays an essential role in human resource development. This study aims to determine the productivity and efficiency of echelon IV employees of the Food Crops, Horticulture Service. And Animal Husbandry in the Jambi Provincial Government as the implementation of Permendagri Number 99 of 2018. The research uses a quantitative descriptive approach. Adequate working time in one year but already has sufficient active time, namely in the Processing and Marketing section of Food Crops and Horticulture Products. There are 7 (seven) sections that have excess productive and efficient working hours but lack staff, namely (1) Animal Feed Breeding and Production Section; (2) Section for Processing and Marketing of Livestock Products; (3) Section for Animal Disease Control and Eradication and Animal Source and Health Institutions; (4) Veterinary Public Health and Animal Protection Section; (5) Section for Observing Animal Diseases and Controlling Drugs; (6) Land and Irrigation Section and (7) Fertilizer, Pesticide, and Financing Section. There are 5 (five) sections that have productive and effective working hours and excess employees, namely (1) Animal Feed Section, (2) Food Crop Production Section; (3) Horticultural Production Section; (4) Food Crop Product Processing, and Marketing Section and Horticulture excess and (5) Section of Machinery and Equipment Tools. The workload is mainly in the Livestock Sector, Processing and Marketing Section of Livestock Products